An Analysis of Lexical Features, Rhetorical Elements, and Character Study in a Novel by Tere Liye - Gusar, Martua Reynhat Sitanggang; Situmorang, Mulkan Andika; Sidabutar, Yanti Arasi; Gultom, Meliana Br.; Panggabean, Sarma (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
This study aims to analyze the lexical features, rhetorical elements and character studies in the novel Sesuk by Tere Liye. This novel contains various lexical features and language styles, which enrich the reading experience. In terms of diction, the use of connotative and descriptive words provides deeper meaning and helps readers imagine the situation described. The research method used in this study is a qualitative method. The results show that language styles such as simile, metaphor, and personification add depth to the meaning and imagery in the story, allowing readers to feel the character's mood. The theme of this novel focuses on the responsibility and maturity of a girl who faces various life challenges, with a progressive storyline and slowly developing tension. The setting and first point of view help readers understand the feelings of the main character, Gadis, more intimately. The study implications, including the importance of affection and responsibility, are very relevant and invite readers to reflect on family values and the impact of our actions. With a subtle delivery, Sesuk invites readers to better understand interpersonal relationships and moral valuesthat exist in everyday life.